Repair Bond Strength of Aged Resin Composite after Different Surface and Bonding Treatments - Wendler, Michael (Materials (Basel), 2016)
The aim of this study was to compare the effect of different mechanical surface treatments and chemical bonding protocols on the tensile bond strength (TBS) of aged composite. Bar specimens were produced using a nanohybrid resin composite and aged in distilled water for 30 days. Different surface treatments (diamond bur, phosphoric acid, silane, and sandblasting with Al(2)O(3) or CoJet Sand), as well as bonding protocols (Primer/Adhesive) were used prior to application of the repair composite. TBS of the specimens was measured and the results were analyzed using analysis of variance (ANOVA) and the Student–Newman–Keuls test (α = 0.05). Mechanically treated surfaces were characterized under SEM and by profilometry. The effect of water aging on the degree of conversion was measured by means of FTIR-ATR spectroscopy. An important increase in the degree of conversion was observed after aging. No significant differences in TBS were observed among the mechanical surface treatments, despite variations in surface roughness profiles. Phosphoric acid etching significantly improved repair bond strength values. The cohesive TBS of the material was only reached using resin bonding agents. Application of an intermediate bonding system plays a key role in achieving reliable repair bond strengths, whereas the kind of mechanical surface treatment appears to play a secondary role.